2011
DOI: 10.1007/s11104-011-0889-5
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing white lupin (Lupinus albus L.) adaptation to calcareous soils through selection of lime-tolerant plant germplasm and Bradyrhizobium strains

Abstract: Aims This study aimed to determine whether white lupin adaptation to moderately calcareous soils could be enhanced by lime-tolerant plants and Bradyrhizobium strains. Methods Fourteen landraces from Italy, Morocco and Egypt and some cultivars were grown in moderatelime (ML) and low-lime (LL) soil with each of two inoculants, one commercial and one including three Bradyrhizobium strains well-nodulating under ML soil (isolated from other lupin species). Grain yield and above-ground biomass were assessed in large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Indeed, Bradyrhizobium has been isolated from root nodules of L. cosentinii in Morocco (Thami Alami et al . ; Annicchiarico and Thami‐Alami ), but, to our knowledge, this is the first report on the isolation of Microvirga from L. cosentinii naturally occurring in the Maamora forest.…”
Section: Discussionmentioning
confidence: 85%
“…Indeed, Bradyrhizobium has been isolated from root nodules of L. cosentinii in Morocco (Thami Alami et al . ; Annicchiarico and Thami‐Alami ), but, to our knowledge, this is the first report on the isolation of Microvirga from L. cosentinii naturally occurring in the Maamora forest.…”
Section: Discussionmentioning
confidence: 85%
“…Tang et al (1995) found that lime‐induced chlorosis in L. angustifolius is not associated with calcium sensitivity, because the same concentration of calcium provided as calcium sulfate has no inhibitory effect, although it does enhance calcium concentrations in leaves. White lupines vary genetically in their tolerance of calcareous soil; therefore, breeding for this trait is an option (Christiansen et al, 1999; Liu and Tang, 1999; Raza et al, 2001; Annicchiarico and Thami Alami, 2011).…”
Section: Soil‐type Adaptationsmentioning
confidence: 99%
“…Summer drought and progressive soil salinization are major climatic stresses in Mediterranean areas, yet information is lacking on the intrinsic genetic variation for drought tolerance, particularly in white lupin. Poor adaptation to calcareous soils is probably the main limit to the crop expansion, but white lupin landraces from Egypt or Italy that display tolerance to free calcium have been identified ( Annicchiarico and Thami-Alami, 2012 ). The primary source of phosphate fertilizer (mined rock phosphate) is considered likely to be depleted within 40 years, emphasizing the importance of sustainable P management.…”
mentioning
confidence: 99%